SEMINAR ISLAMI KONSTRUKSI KAJIAN FIQH MUAMALAH RUMAH TANGGA DI KAMPUNG PALESTINE - Farah Diba; Duna Izfanna; Ahmadih Rojali (Bajang Institute, 2022)
The Islamic seminar program which was held with the aim of constructing the study of household muamalah fiqh in the Palestine village. The basis of this seminar program is based on observations and interviews with residents about their daily lives as a dual-earner couple. Dual earner couples are closely related to the conflict of unequal division of roles in the house and are struggling with mere routines so that the function and meaning of a family needs to be lived in it. The method used is the lecture method with construction framing scheme, namely problem identification, causal interpretation, moral judgment, and suggestions for improvement which are reviewed with various construction variations that relate to everyday life, both simplification, association, generalization and classification. The conclusions obtained by the participants were easy to understand from the language presented, with the arguments presented making the participants curious in to learn and finally, the participants instilled the mindset of the ultimate goal of building a sakinah family.